2012
DOI: 10.1017/s003329171200236x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with bipolar disorders share similar but attenuated prospective memory impairments with patients with schizophrenia

Abstract: Patients with bipolar disorder shared a similar PM impairment with those with schizophrenia. Findings of this study extended the similarity in neurocognitive impairments between the two psychiatric disorders to PM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
(70 reference statements)
3
13
1
Order By: Relevance
“…Chan et al. () made the first attempt to compare PM between schizophrenia and bipolar disorder. These investigators used laboratory‐based PM tasks and found similarities of PM performance in the two diagnostic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al. () made the first attempt to compare PM between schizophrenia and bipolar disorder. These investigators used laboratory‐based PM tasks and found similarities of PM performance in the two diagnostic groups.…”
Section: Discussionmentioning
confidence: 99%
“…The modified version of the original computerized “dual‐task” PM paradigm (Wang et al, ) was used to objectively assess time‐ and event‐based PM. The details of this paradigm (Lui et al, ; Wang et al, ) and the rationale for the development of this modified version (Chan et al, ) have been described elsewhere. In the time‐based PM session, the ongoing task was a lexicon‐decision task, which required participants to view a series of four‐character phrases in Chinese presented on the computer screen at a rate of one phrase every 4 seconds, and to decide whether the phrases were idioms or not, by pressing two pre‐specified response buttons.…”
Section: Methodsmentioning
confidence: 99%
“…Other defi cits identifi ed concerned associative learning (Brambilla et al 2011 ), delayed memory (Dittmann et al 2008a ;Ha et al 2012 ;Zubieta et al 2001 ;Seidman et al 2002 ;Bora et al 2007 ;Martinez-Aran et al 2008 ;Basso et al 2009 ;Hill et al 2009 ;Dittmann et al 2008b ), nonverbal memory (Deckersbach et al 2004a ), visual memory (Langenecker et al 2010 ;Sanchez-Morla et al 2009 ;Xu et al 2012 ;Goldberg et al 1993 ;Coffman et al 1990 ;Zubieta et al 2001 ;Fitzgerald et al 2004 ;Ali et al 2000 ) and autobiographical (Scott et al 2000 ) and prospective memory (Chan et al 2012 ).…”
Section: Learning and Memorymentioning
confidence: 99%
“…The limited literature suggests that in general, the patients' self-reports of impairment do not correlate or predict objective neuropsychological defi cits (Burdick et al 2005 ;Chan et al 2012 ;van der Werf-Eldering et al 2011 ). Maybe there is some weak correlation between subjective complains and defi cits in attention, memory and execute function .…”
Section: Awareness Of the Neurocognitive Deficitmentioning
confidence: 99%